Pengembangan Produk Permen Jelly Jamu Kunyit Asam Industri Rumah Tangga Jamu di Sleman Yogyakarta - Dian Eka Ermawati; Wisnu Kundarto; Yeni Farida (Universitas Mathla'ul Anwar Banten, 2022)
PRODUCT DEVELOPMENT OF GUMMY OF TURMERIC ACID JAMU PRODUCTION BY HERBAL HOMINDUSTRY IN SLEMAN YOGYAKARTA. Jamu of turmeric acid is an Indonesian herbal drink made from turmeric and tamarind. The home industry in Sleman Yogyakarta produces turmeric acid jamu and promising to develop as gummy. The Consumers of turmeric acid Jamu are limited, Children who want to consume jamu are rarely, whereas curcumin in turmeric can increase appetite, especially for school-age children. Product innovation is needed to process jamu become more desirable, durable, and still efficacious, for example, jelly candy or gummy. Gummy is made with the addition of gelling agent that made texture is chewy. Carrageenan is a gelling agent made from seaweed and safe for food products. The aims of product development are to develop micro businesses and to improve the economy and public confidence in the quality of herbal medicine especially jamu. Gummy formulation with carrageenan and turmeric acid jamu as the main ingredient. Formula with 8.0% carrageenan is the optimum formula because it meets the quality requirements for gummy and is most preferred by respondents.